Nearly Carbon Neutral Conferences in a Time of Pandemic: A Review Essay - Bidgood, Lee (Lidé města, 2020)
Before the COVID-19 pandemic, we often gathered as scholars. We talked, ate, drank, chatted, argued, and learned together at annual meetings. En route, we would likely have taken a series of flights from our particular local airport that would gradually surround us with more and more people who do what we do; at a larger regional or international hub, we might find ourselves on a flight filled with colleagues and professional acquaintances all headed for the same conference – finishing up presentations on laptops, catching each other up on the latest disciplinary news and gossip.